Treatment of waste marine clay by alkaline-activated ground granulated blast-furnace slag and municipal solid waste incineration bottom ash - Saiou Fu; Ping Wang; Shiyu Liu; Qianshen Ding; Lei Lang; Lijun Han; Xin Chen; Jiangshan Li (Journal of Rock Mechanics and Geotechnical Engineering)
The construction of coastal areas generates a substantial volume of waste marine clay (WMC), which poses environmental and safety challenges during the stockpiling process. The improved preparation of WMC as roadbed materials emerges as a crucial pathway for resource utilization. However, the engineering performance and durability of roadbed materials prepared from WMC have always been a concern for scholars and engineers. This study employs alkali-activated ground granulated blast-furnace slag (GGBFS) and municipal solid waste incineration bottom ash (MSWIBA) to solidify WMC for preparation of the roadbed materials. The results showed that the combined utilization of alkali-activated GGBFS and MSWIBA to improve WMC can meet the environmental and mechanical requirements of roadbed materials. The incorporation of 5–20% MSWIBA could improve the water stability coefficient and California bearing ratio to more than 85% and 80%, respectively. The durability of roadbed material was significantly improved by addition of MSWIBA. After 12 dry–wet cycles, the strength of the material without MSWIBA and with 5% MSWIBA was 0 and 2.87 MPa, respectively. Following analysis of engineering properties and durability, the optimal dosage of MSWIBA was determined to be 5%. The enhanced durability can be attributed to the optimization of material gradation and pore structure achieved through the incorporation of a small quantity of MSWIBA. The carbon emission and normalized global warming potentials of roadbed material treated by MSWIBA and GGBFS were much lower than that of cementitious binders such as ordinary Portland cement. These findings indicate that MSWIBA has the potential to substitute natural aggregates like sand and gravel, effectively improving the durability of roadbed materials and promoting the safe and efficient recycling of solid waste resources.